Role of α2-Adrenoceptors in Hypertension: Focus on Renal Sympathetic Neurotransmitter Release, Inflammation, and Sodium Homeostasis - Hering, Lydia; Rahman, Masudur; Potthoff, Sebastian A.; Rump, Lars C.; Stegbauer, Johannes (Frontiers in Physiology, 2020)
The kidney is extensively innervated by sympathetic nerves playing an important role in the regulation of blood pressure homeostasis. Sympathetic nerve activity is ultimately controlled by the central nervous system. Norepinephrine, the main sympathetic neurotransmitter, is released at prejunctional neuroeffector junctions in the kidney and modulates renin release, renal vascular resistance, sodium and water handling as well as immune cell response. Under physiological conditions, renal sympathetic nerve activity (RSNA) is modulated by peripheral mechanisms such as the renorenal reflex, a complex interaction between efferent sympathetic nerves, central mechanism and afferent sensory nerves. RSNA is increased in hypertension and therefore critical for the perpetuation of hypertension and the development of hypertensive kidney disease. Renal sympathetic neurotransmission is not only regulated by RSNA, but also by prejunctional α2-adrenoceptors. Prejunctional α2-adrenoceptors serve as autoreceptors which, when activated by norepinephrine, inhibit the subsequent release of norepinephrine induced by a sympathetic nerve impulse. Deletion of α2-adrenoceptors aggravates hypertension ultimately by modulating renal pressor response and sodium handling. α2-adrenoceptors are also expressed in the vasculature, renal tubules and immune cells and exert thereby effects related to vascular tone, sodium excretion and inflammation. In the present review, we highlight the role of α2-adrenoceptors on renal sympathetic neurotransmission and its impact on hypertension. Moreover, we focus on physiological and pathophysiological functions mediated by non-adrenergic α2-adrenoceptors. In detail, we discuss the effects of sympathetic norepinephrine release and α2-adrenoceptors activation on renal sodium transporters, on renal vascular tone and on immune cells in the context of hypertension and kidney disease.